Western Muslims and the future of Islam - Ramadan, Tariq (Oxford University Press, 2004)
Ramadan's goal is to create an independent Western Islam, anchored not in the traditions of Islamic countries but in the cultural reality of the West. He begins by offering a fresh reading of Islamic sources, interpreting them for a Western context and demonstrating how a new understanding of universal Islamic principles can open the door to integration into Western societies. He then shows how these principles can be put to practical use. Ramadan contends that Muslims can-indeed must-be faithful to their principles while participating fully in the civic life of Western secular societies. Grounded in scholarship and bold in its aims, Western Muslims and the Future of Islam offers a striking vision of a new Muslim Identity, one which rejects once and for all the idea that Islam must be defined in opposition to the West